2003
DOI: 10.1128/jcm.41.5.2197-2200.2003
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum β-Lactamase Enzymes in Clinical Isolates ofEnterobacterSpecies from Lagos, Nigeria

Abstract: Over a 9-month period, 8 of 40 nonduplicate isolates of Enterobacter spp. producing extended-spectrum ␤-lactamase (ESBL) were detected for the first time from two hospitals in Lagos, Nigeria. Microbiologic and molecular analysis confirmed the presence of ESBL. Only four isolates transferred ESBL resistance as determined by the conjugation test, and pulsed-field gel electrophoresis showed genetically unrelated isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
54
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 30 publications
11
54
6
Order By: Relevance
“…This is higher than the 2.7 %, 15.8 %, 20 % and 28.9 % reported in previous studies in Nigeria [8,12,18,19]. Previous use of antimi-crobial agents, especially cephalosporins and fluoroquinolones, has been reported as risk factors associated with emergence of ESBL [6,7].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This is higher than the 2.7 %, 15.8 %, 20 % and 28.9 % reported in previous studies in Nigeria [8,12,18,19]. Previous use of antimi-crobial agents, especially cephalosporins and fluoroquinolones, has been reported as risk factors associated with emergence of ESBL [6,7].…”
Section: Discussioncontrasting
confidence: 52%
“…The finding that Gram negative bacteria from wound and urine specimens produce ESBL agrees with previous reports [5,19]. Enterobacter species were the most prevalent producers of ESBL generally and from both wounds and urinary tract infections as previously reported from this study locality [12] and disagrees with others which reported Escherichia coli and Klebsiella species as the predominant producers [20].…”
Section: Discussioncontrasting
confidence: 40%
“…was 12.73% which was different from the other results in Pakistan (50%, 14.93%) (21,22), Nigeria (37.5%) (10) and Pennsylvania, the USA (33.33%) (9).…”
Section: Discussioncontrasting
confidence: 54%
“…In Nigeria, these enzymes have been reported in Enterobacter species from human patients in Lagos (1).…”
Section: Introductionmentioning
confidence: 99%